SITUATIONAL ANALYSIS OF THE PRODUCTION OF ELECTRIC ENERGY AND ITS ASSOCIATION WITH THE ENERGY OVERCAPACITY IN THE PERUVIAN ELECTRIC MARKET - MEZA ZAMATA, JESSICA ROSARIO (2024)
IN PERU, THE ENERGY MARKET IS CONTINUALLY AFFECTED BY THE DIFFERENT POLICIES IN THIS SECTOR, THE HEALTH CRISIS AND THE CONTINUOUS SOCIAL UPHEAVALS THAT ARE FACTORS THAT DRIVE AN ENERGY OVERSUPPLY. THE OBJECTIVE OF THIS RESEARCH IS TO CARRY OUT A STUDY OF THE PERUVIAN ELECTRICITY MARKET TO UNDERSTAND THE FACTORS THAT ARE RELATED TO THE OVERSUPPLY OF ENERGY GENERATION IN THE PERUVIAN ELECTRICITY MARKET. TO DO THIS, THE PERUVIAN ELECTRICITY MARKET, ITS CHARACTERISTICS, SUPPLY AND DEMAND FOR ELECTRICITY GENERATION ARE STUDIED. IN ADDITION, THE CURRENT LEGAL FRAMEWORK IS DESCRIBED IN ORDER TO FACILITATE UNDERSTANDING OF THE OPERATION OF THE CORRESPONDING ACTIVITIES. IT IS CONCLUDED THAT A DECREASING SPOT PRICE AND AN OVERSUPPLY OF GENERATION MAKE THE ENTRY OF NEW BASE GENERATORS UNATTRACTIVE. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.